MERUDUKSI KECEMASAN BELAJAR SISWA MELALUI KONSELING INDIVIDU BERBASIS CYBER COUNSELING - Suehartono Syam (Akademika, 2020)
There are two objectives of this study, to describe student learning anxiety before and after the intervention, and to find out whether or not cyber counseling-based individual counseling can reduce student learning anxiety. The research method used is quantitative research with experimental design. A total of 7 students are involved and asked in this study. Data collection was carried out by two methods, questionnaires and observation. There is two data analysis used, descriptive and inferential analysis. The results of the study found that students who previously in high and very high categories for learning anxiety yet after the intervention decreased to the medium and low categories. This study showed that individual cyber counseling-based could reduce learning anxiety because of the positive impact it had on the students.